Arsole‐Containing π‐Conjugated Polymer by the Post‐Element‐Transformation Technique. Issue 48 (7th November 2016) - Matsumura, Yoshimasa; Ishidoshiro, Makoto; Irie, Yasuyuki; Imoto, Hiroaki; Naka, Kensuke; Tanaka, Kazuyoshi; Inagi, Shinsuke; Tomita, Ikuyoshi
Abstract: A synthetic method to obtain an arsole‐containing π‐conjugated polymer by the post‐transformation of the organotitanium polymer titanacyclopentadiene‐2, 5‐diyl unit with an arsenic‐containing building block is described. The UV/Vis absorption maximum and onset of the polymer were observed at 517 nm and 612 nm, respectively. The polymer exhibits orange photoluminescence with an emission maximum ( E max ) of 600 nm and the quantum yield ( Φ ) of 0.05. The polymer proved to exhibit a quasi‐reversible redox behavior in its cyclic voltammetric (CV) analysis. The energy levels of the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) were estimated to be −5.43 and −3.24 eV, respectively, from the onsets for oxidation and reduction signals in the CV analysis. Further chemical modification of the arsole unit in the π‐conjugated polymer by complexation of gold(I) chloride occurred smoothly resulting in the bathochromic shift of the UV/Vis absorption and lowering of the LUMO energy level. Abstract : Colorful polymer : An arsole‐containing π‐conjugated polymer was prepared by reacting the titanacyclopentadiene unit of an organometallic polymer with an arsenic‐containing building block. The resulting polymer exhibits a low LUMO energy level, quasi‐reversible redox behavior, and an excellent ability to coordinate gold(I) chloride.